026 Does the oslo sports trauma research center shoulder injury prevention program affect the risk factors external rotation strength and internal rotation range of motion? A randomized controlled study among adolescent handball players. (3rd March 2020) - Fredriksen, Hilde; Cools, Ann; Bahr, Roald; Myklebust, Grethe
Abstract : Background: Shoulder problems are common in handball, but preventable. However, player compliance remains a challenge, as the existing prevention program is time consuming. Objective: To assess the effect of the Oslo Sports Trauma Research Center shoulder injury prevention program on external rotation (ER) strength and internal rotation (IR) range of motion (ROM), believed to represent key risk factors for injury. Design: Randomised controlled trial, single blinded. Setting: Youth handball players (16–18 yrs). Participants: Four youth handball teams (three female, one male, 57 players, mean age 17.1 yrs) were randomly selected from eligible teams in the Oslo region, and randomized to an intervention group (28 players) or control group (29 players). Interventions: The Oslo Sports Trauma Research Center shoulder injury prevention program was implemented during regular handball warm-up three times a week for 18 weeks in the intervention group. Main outcome measurements: The main outcome variable was the between-group difference in ER strength and IR ROM change from baseline to post intervention. Isometric ER strength was measured with a handheld dynamometer and IR ROM with a digital goniometer. Results: Mean dominant shoulder isometric ER strength increased significantly both in the intervention (10%) and the control group (6%) during the intervention, but there was no significant group by time interaction (group difference: 0.06 N/kg (95% CI: -0.04 to 0.17). IR ROM did not change in either group during the intervention. Conclusions: The Oslo Sports Trauma Research Center shoulder injury prevention program did not affect the risk factors ER strength and IR ROM. The preventive effect of the program must therefore be due to other factors.